2003
DOI: 10.1016/s0028-3932(03)00060-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-identical neural mechanisms for two types of mental transformation: event-related potentials during mental rotation and mental paper folding

Abstract: Reaction times, accuracy and 128-channel event-related potentials (ERPs) were measured from 14 normal, right-handed subjects while they performed two different parity-judgment tasks that require transformations of mental images: a relatively simple task requiring a single transformation (mental letter rotation), and a more complex task involving a coordinated sequence of transformations (mental paper folding). Reaction times increased monotonically with larger angular displacements from the upright (for mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 45 publications
5
33
1
Order By: Relevance
“…1997; Milivojevic et al, 2003). These latter neural mechanisms classically are observed at a somewhat later time period of 450 -700 ms in the region of the IPS (Pegna et al, 1997;Harris et al, 2000;Jordan et al, 2001;Gauthier et al, 2002;Podzebenko et al, 2002;Harris and Miniussi, 2003) as also supported by our present findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…1997; Milivojevic et al, 2003). These latter neural mechanisms classically are observed at a somewhat later time period of 450 -700 ms in the region of the IPS (Pegna et al, 1997;Harris et al, 2000;Jordan et al, 2001;Gauthier et al, 2002;Podzebenko et al, 2002;Harris and Miniussi, 2003) as also supported by our present findings.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, because our evoked potential study showed OBTrelated activity at ϳ350 ms and previous studies revealed that mental transformation of objects takes place between ϳ400 and 600 ms after stimulus onset (Pegna et al, 1997;Milivojevic et al, 2003), we expected TMS pulses to interfere with mental transformations at these latencies and therefore collapsed the data for the SOAs of 100 -300, 350 -550, and 600 -800 ms (each time window consisting of 5 time bins). These data were subjected to repeated measure ANOVAs, with the factors TMS site (TPJ vs IPS), task (OBT vs LT), stimulus orientation (back-facing/unturned vs front-facing/turned), and SOA (100 -300/350 -550/600 -800 ms).…”
Section: Transcranial Magnetic Stimulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…An event-related potentials study showed that, in comparison with multiplication, addition elicited smaller late positive potentials at the right posterior electrodes (Zhou et al, 2009). The smaller late positive potentials have been linked to greater visuospatial processing in previous ERP studies (e.g., Heil & Rolke, 2002;Milivojevic et al, 2003;Núñez-Peña et al, 2005;Yoshino et al, 2000). To our knowledge, the dissociation between subtraction and multiplication at the right parietal cortex has been reported only in one previous neuropsychological study (e.g., Dehaene & Cohen, 1997).…”
Section: Discussionmentioning
confidence: 72%
“…These revealed an activation of parietal cortex, either exclusively in the right hemisphere (Harris et al, 2000;Harris and Miniussi, 2003), the left hemisphere (Alivisatos and Petrides, 1997; Vingerhoets et al, 2001), or bilaterally (Carpenter et al, 1999). Studies measuring event-related potentials (ERPs) during the mental transformation of external objects revealed a negative component located over parietal scalp electrodes (Peronnet and Farah, 1989;Wijers et al, 1989;Yoshino et al, 2000;Milivojevic et al, 2003). Using evoked potential mapping (EP mapping) and electrical neuroimaging, Pegna et al (1997) found a topographic pattern (or EP map) between 400 and 600 ms that increased in duration for greater angles of rotation and was localized to right parieto-occipital cortex.…”
mentioning
confidence: 99%